2012
DOI: 10.4038/sjae.v10i0.4590
|View full text |Cite
|
Sign up to set email alerts
|

Time Preference and Natural Resource Use by Local Communities: The Case of Sinharaja Forest in Sri Lanka

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…As such, although these farmers have some private incentive to conserve soil quality stock, they are still forced to overexploit the soil quality stock as they maximise current incomes at the expense of future wellbeing. This result confirms similar results by Hausman (1979), Holden et al (1998) and Gunatilake et al (2007) indicating that poverty (income) is an important determinant of the marginal rate of substitution between current and future consumption. Up to three-quarters of Malawi's 13.1 population live below the international poverty line of $1.25 dollars a day (World Development Indicators 2011).…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…As such, although these farmers have some private incentive to conserve soil quality stock, they are still forced to overexploit the soil quality stock as they maximise current incomes at the expense of future wellbeing. This result confirms similar results by Hausman (1979), Holden et al (1998) and Gunatilake et al (2007) indicating that poverty (income) is an important determinant of the marginal rate of substitution between current and future consumption. Up to three-quarters of Malawi's 13.1 population live below the international poverty line of $1.25 dollars a day (World Development Indicators 2011).…”
Section: Resultssupporting
confidence: 94%
“…Time preference is defined as the marginal rate of substitution between current and future consumption(Becker and Mulligan 1997;in Gunatilake et al 2007). …”
mentioning
confidence: 99%
“…For example, Ghanaian fishers had an average annual discount rate of 130% [16], while discount rates for farmers in Madagascar ranged from 117% to 208% [20], and Bolivian horticulturists had extremely high rates of between 4380% and 5110% [56]. Lower annual rates ranged from 13% and 34% for forest users in Sri Lanka [19], to 35-61% for farmers in the Philippines [59]. It should be noted that comparing discount rates across studies is complicated due to methodological differences [60].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 94%
“…For example, Gunatilake et al [19] found that in Sri Lanka, individuals with higher rates of time preference caused forest resource depletion, while Casse et al [20] found that observed discount rates of inhabitants in highly deforested areas were significantly higher than those living in other areas. Further, Ethiopian farmers with higher discount rates were less likely to invest in soil conservation practices [21].…”
Section: Introductionmentioning
confidence: 97%
“…Atmadja and Sills found that personal discount rates were significant in explaining harvest decisions of limited-resource, non-industrial private forestland owners in India and the USA [17]. Gunatilake, Wickramasinghe, and Abeygunawardena [102] found statistically significant effects between the rates of time preference on the harvesting of non-timber forest products in Sri Lanka, and Godoy et al [96] estimated the internal rate of time preference of Bolivian farmers living near forests and related it to the rate of forest clearance. When rates of time preferences are independently estimated, they are commonly found to be correlated with socio-economic attributes such as education [102,103], age [17] and wealth [17,103], which in turn are related to forest management behaviour.…”
Section: The Endogenous Shadow Price Of Timementioning
confidence: 99%